2018
DOI: 10.1186/s12935-018-0666-0
|View full text |Cite
|
Sign up to set email alerts
|

Genome editing of oncogenes with ZFNs and TALENs: caveats in nuclease design

Abstract: BackgroundGene knockout technologies involving programmable nucleases have been used to create knockouts in several applications. Gene editing using Zinc-finger nucleases (ZFNs), Transcription activator like effectors (TALEs) and CRISPR/Cas systems has been used to create changes in the genome in order to make it non-functional. In the present study, we have looked into the possibility of using six fingered CompoZr ZFN pair to target the E6 gene of HPV 16 genome.MethodsHPV 16+ve cell lines; SiHa and CaSki were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
(31 reference statements)
1
14
0
Order By: Relevance
“…They were further proved to be clinically more efficient as they could also establish their therapeutic effect in xenograft mouse model (Ding et al, 2014). Shankar et al (2018) reported that they could not successfully inhibit E6 expression and activity using ZFNs as no matching target sequence could be obtained using publicly available computer software. Thus, they used TALENs instead of the same purpose.…”
Section: Zinc-finger Nucleasesmentioning
confidence: 99%
See 1 more Smart Citation
“…They were further proved to be clinically more efficient as they could also establish their therapeutic effect in xenograft mouse model (Ding et al, 2014). Shankar et al (2018) reported that they could not successfully inhibit E6 expression and activity using ZFNs as no matching target sequence could be obtained using publicly available computer software. Thus, they used TALENs instead of the same purpose.…”
Section: Zinc-finger Nucleasesmentioning
confidence: 99%
“…It resulted in a corresponding increase in the amount of pRb and a decrease in p14ARF, the downstream targets following a necrotic pathway of cell death as shown through the upregulation of RIP-1, Cyclophilin A, and LDH-A. In the due course, another study by Shankar et al (2018) reported that TALEN-mediated editing of HPV16 E6 did not yield any editing activity, while E7 could be successfully knocked down in HPV16 infected CasKi cells. E6-targeted TALEN was composed of 18 modules on both the arms spaced by a 19 nucleotide region, while the E7 targeting TALEN contained 18 modules on both the ends separated by a 21 nucleotide gap.…”
Section: Transcription Activator-like Effector Nucleasementioning
confidence: 99%
“…On the other hand, there are transcription activatorlike effector nucleases (TALENs); these ones arise from the binding of a DNA binding domain and a nuclease catalytic domain of Fok1 (47). Using gene editing techniques such as ZFNs and specific TALENs, has been specifically inhibiting cervix cancer cell growth (48)(49)(50) and acute lymphoblastic leukemia (45,51). As well, ZFNs have been used for fighting the resistance to therapeutic agents in breast cancer cells (52).…”
Section: Gene Editing Techniques In Cancermentioning
confidence: 99%
“…A preprint manuscript that targeted HPV18 E6 and E7 genes with CRISPR/Cas explored the anti-tumor mechanisms [ 47 ], and, contrary to other studies, apoptotic features were no present but instead markers of senescence were observed. Shankar et al [ 48 , 49 ], tested TALENs to HPV16 E7, and observed a distinct lack of apoptosis, but instead features of cell cycle arrest and necrosis. Collectively, these studies show that a pleiotropic route to tumor inhibition occurs upon oncogene inactivation in HPV-related cancers.…”
Section: Human Papillomavirusmentioning
confidence: 99%